Deficits of white matter axial diffusivity in bipolar disorder relative to major depressive disorder: No relationship to cerebral perfusion or body mass index. (2nd November 2019) - Lan, Martin J.; Rubin‐Falcone, Harry; Sublette, M. Elizabeth; Oquendo, Maria A.; Stewart, Jonathan W.; Hellerstein, David J.; McGrath, Patrick J.; Zanderigo, Francesca; Mann, J. John
Abstract: Objective: To compare white matter integrity (WMI) in bipolar disorder (BD) relative to healthy volunteers (HVs) and major depressive disorder (MDD). To determine the relationship of bipolar‐specific differences in WMI to cerebral perfusion, body mass index (BMI), and blood pressure as indices of cardiovascular function. Methods: Thirty‐two participants with BD, 44 with MDD, and 41 HV were recruited. All BD and MDD participants were in a major depressive episode, and all but 12 BD participants were medication‐free. 64‐direction diffusion tensor imaging (DTI) and arterial spin labeling (ASL) sequences were obtained. Tract‐based spatial statistics (TBSS) on four DTI indices were employed to distinguish patterns of DTI in BD relative to HV and MDD groups. BMI, blood pressure, and medical histories were also obtained for the BD participants. Results: A cluster of lower axial diffusivity (AD) was found in BD participants in comparison to the HVs in the left posterior thalamic radiation, superior longitudinal fasciculus, inferior longitudinal fasciculus, fronto‐occipital fasciculus, and internal capsule. Mean AD in the significant cluster was not associated with cerebral blood flow (CBF) in the region as measured by ASL, and was not associated with BMI or blood pressure. A cluster of lower AD was also found in the BD group when compared to MDD that had spatial overlap with the HV comparison. Conclusions: The results indicate a deficit of AD in BD when compared to MDD and HV groups. No association between AD values and either cerebral perfusion, BMI, or blood pressure was found in BD.